2017
DOI: 10.1177/0885328217715363
|View full text |Cite
|
Sign up to set email alerts
|

Study of composite vascular scaffold combining with differentiated VSMC- and VEC-like cells in vitro and in vivo

Abstract: Although research into the tissue engineering of vessels has proceeded at a tremendous pace, many deficiencies still need to be resolved. A well-adopted constructed vessel requires both functional and structural properties to stimulate the native vessel and resist stress and tension in vivo. In the present study, we developed a novel three-layer composite vascular scaffold consisting of differentiated vascular smooth muscle cell-, vascular endothelial cell-like cells, and a rabbit acellular vascular matrix (AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In our previous studies, human-like collagen I (HLC-I) (23) was combined with the acellular vascular matrix (ACVM) (23,24) to construct the ACVM-0.25% HLC-I scaffold material (25). This process involved combining a polymer material with natural degenerative biomaterials to construct a composite tissue engineering scaffold material.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies, human-like collagen I (HLC-I) (23) was combined with the acellular vascular matrix (ACVM) (23,24) to construct the ACVM-0.25% HLC-I scaffold material (25). This process involved combining a polymer material with natural degenerative biomaterials to construct a composite tissue engineering scaffold material.…”
Section: Introductionmentioning
confidence: 99%
“…This process involved combining a polymer material with natural degenerative biomaterials to construct a composite tissue engineering scaffold material. This material supports the growth of seed cells with a three-dimensional ultrastructure of protein space to promote the formation of functional tissue, but it also possesses compressive mechanical properties required for vascular tissue engineering (25). A previous study demonstrated that vascular endothelial cells and vascular smooth muscle cells are induced and differentiated by human gingival fibroblasts (HGFs) (25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ACVM-0.25% HLC-I scaffold was prepared on the basis of previous studies [14,15]. The third-generation of HGFs with good growth condition was collected, digested at 0.25% trypsin (Sigma Biotechnology) 37 C for 5 min, and then centrifuged at 1000 rpm/min to remove supernatant and adjust cell concentration to 1 Â 10 6 cells/mL.…”
Section: Preparation Of Hgecs-hgfs-vecs-acvm-025% Hlc-i Composite Scmentioning
confidence: 99%
“…In this study, human gingival fibroblasts (HGFs), human gingival epithelial cells (HGECs) and vascular endothelial-like cells (VEC-like cells) [12] were used as seed cells in combination with ACVM-0.25% HLC-I [13][14][15][16] to construct tissueengineered vascularised oral mucosa-like structures in vitro and in vivo, and attempted to establish deep blood vessel connections through vascularisation, aiming at repairing tissue damage.…”
Section: Introductionmentioning
confidence: 99%